Implementation of the Adiwiyata Program to Build Environmental Caring Character in Elementary School Students - Fazira, Nurul; Ramadan, Zaka Hadikusuma (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The Adiwiyata program is a program to create an ideal living environment for students in order to achieve learning goals between teachers and students. The aim of this research is to analyze the implementation of the Adiwiyata program in building environmentally caring characters in students. Descriptive qualitative research with a case study approach was used in this research. Because the provincial-level Adiwiyata Program had just been introduced, the research location was at SDN 176 Pekanbaru. The results of this research show that when the Adiwiyata activity program is put into practice, student character is not the only thing that is important. They also need to have a disciplined attitude towards the environment, understand their responsibilities towards the environment, and get used to these activities from an early age. So that, in the end, it becomes a positive culture and children's environmental awareness becomes embedded in their daily lives.